ANALISIS USER INTERFACE MAXIMOM BERBASIS USER PERSONA DENGAN MENGGUNAKAN PENDEKATAN GOOGLE DESIGN SPRINT - Sicillya Setya Jayani Santosa; Tri Sagirani; Vivine Nurcahyawati (Jurnal Teknologi dan Terapan Bisnis, 2020)
Providing qualified domestic workers and looking for employers who have good behavior are things that are needed by the community. In addition, the assurance of the contract promised at the beginning of the agreement and its realization from the perspective of the employer and domestic worker is something that must be considered. With Maximom present as the answer needed by the public, Maximom utilizes a website-based application in the form of a company profile and dashboard to convey value and maintain performance to customers. In order to determine the characteristics and needs of users, the author uses the User Persona tool to focus on target users who will operate the display system. It is intended that the resulting UI display matches the expectations of each potential user. The approach that the author applies to UI design is the Google Design Sprint which is superior in terms of time saving, focus on problems and solving goals (in the form of prototypes), and idea development. The stages in Google Design Sprint are Mapping, Sketching, Deciding, Prototyping, and Testing.